2009
DOI: 10.3171/foc.2009.26.2.e8
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapy in peripheral nerve regeneration: From basic science to clinical study

Abstract: Object This review summarizes the continuous study of low-power laser radiation treatment of a severely injured peripheral nerve. Laser phototherapy was applied as a supportive factor for accelerating and enhancing axonal growth and regeneration after injury or a reconstructive peripheral nerve procedure. In nerve cell cultures, laser phototherapy was used to stimulate activation of nerve cells. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 28 publications
(27 reference statements)
1
36
0
4
Order By: Relevance
“…In the late 1970s, it was reported that laser energy affects the regeneration of traumatically injured peripheral nerves. 13 However, most of the findings on the positive effects of phototherapy on peripheral nerve regeneration have been reported only since the late 1980s, 14,15 in 1987, Rochkind et al applied low-energy He-Ne laser irradiation (LELI, 632.8 nm, 10 J/cm 2 , continuous) on both intact and severely injured peripheral nerves in rats for 20 consecutive days and reported promising electrophysiological and morphological effects. 16 This was followed by a report on decrease in formation of scar tissue at the site of injury 17 and acceleration of the regeneration process of severely injured sciatic nerve and spinal cord.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the late 1970s, it was reported that laser energy affects the regeneration of traumatically injured peripheral nerves. 13 However, most of the findings on the positive effects of phototherapy on peripheral nerve regeneration have been reported only since the late 1980s, 14,15 in 1987, Rochkind et al applied low-energy He-Ne laser irradiation (LELI, 632.8 nm, 10 J/cm 2 , continuous) on both intact and severely injured peripheral nerves in rats for 20 consecutive days and reported promising electrophysiological and morphological effects. 16 This was followed by a report on decrease in formation of scar tissue at the site of injury 17 and acceleration of the regeneration process of severely injured sciatic nerve and spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Most reports on the effect of LLLT on PNS injury are in cases of axonotmesis. [13][14][15][18][19][20][21]25,[29][30][31][32] However, promising results have been obtained in severe cases of neurotmesis when LLLT is used in combination with or Gore-Tex tubes. 27 The cutaneous branch consisted of 400 myelinated and 1800 unmyelinated afferent axons.…”
Section: Introductionmentioning
confidence: 99%
“…Prathap et al [26] found that LLLT of 3 and 4 j/cm 2 was effective for regeneration of both motor and sensory nerve conduction velocity of experimentally induced diabetic neuropathy as compared with control group. Also Rochkind et al [27] found that 15 min application of laser therapy transcutaneously to both the site of nerve injury and to the corresponding segments of the spinal cord improves function recovery and recruitment of voluntary muscle activity. Other studies concluded that laser irradiation allows higher metabolism for nerve, prevents degeneration of motor cell, induces proliferation of Schwann cell, allows and increases myelinization and axon regeneration [13,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research findings suggested that LLL treatment appears to enhance re innervation of target tissues subsequent to nerve injury [41]. Rochkind [42] found that laser improves function recovery and recruitment of voluntary muscle activity through application transcutaneously to the site of nerve injury (15 min) and to the corresponding segments of the spinal cord (15 min).…”
Section: Doi: 107243/2055-2386-4-17mentioning
confidence: 99%